We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
230
1
avatar

Please help to solve  lim(x->1) (sqrt(x+a)+b)/(x^2-1)=1

 

lim(x->1) (sqrt(x+a)+b) / (x^2-1)=1

lim(x->1) (sqrt(x+a)+b) * (sqrt(x+a)-b) / [(x^2-1) * (sqrt(x+a)-b)] = 1

lim(x->1) (x+a-b^2) / [(x-1) * (x+1) * (sqrt(x+a)-b)] = 1

 Sep 17, 2018
edited by Guest  Sep 17, 2018
edited by Guest  Sep 17, 2018
 #1
avatar+102459 
0

Are you asking for a value of a and b that will make this work?

 

\(\displaystyle \lim_{x^-\rightarrow1} \frac{\sqrt{x+a}\;+b}{(x^2-1)}=1\)

 

 

No idea.

 Sep 17, 2018

8 Online Users

avatar
avatar